Determinan Ketahanan Pembiayaan Defisit Anggaran Indonesia Tahun 1998-2022 - Kholis, Nur; Wahyudin, Wahyudin (Seminar Nasional Official Statistics, 2024)
Indonesia's government debt ratio is still below the 60% limit set by law. However, the primary deficit in Indonesia's government budget from 2012-2022 has an increasing trend. Moreover, interest payments from sovereign debt are an additional burden on the government budget. This study examines the sustainability of Indonesia's budget-deficit financing using the Dornbusch Deficit Burden value and the factors that influence it. The Dornbusch Deficit Burden value is interpreted as a change in value of debt-to-GDP ratio. Yearly data used from 1998-2022. The analysis method used is the ARDL-ECM. In the short term, the rupiah exchange rate has negative effect on Dornbusch Deficit Burden value, while in the long term, the rupiah exchange rate has positive effect. The world crude oil price negatively affects Dornbusch Deficit Burden value in short term, while foreign interest rate (Fed Rate), in long and short term, has nonsignificant effect on Dornbusch Deficit Burden value.